Twilight of the American century - Bacevich, Andrew J. (University of Notre Dame Press, 2018)
"Andrew Bacevich is among our most important public intellectuals in politics, foreign policy, international relations, and security. He writes regularly for The Wilson Quarterly, Foreign Affairs, Foreign Policy, The Nation, and The New Republic. His op-eds have appeared in the New York Times, Washington Post, Wall Street Journal, Boston Globe, and Los Angeles Times. This book is a curated edition of his numerous writings on American politics and war after 9/11. This volume will reflect the entirety of the American experience post-9/11, politically, culturally, and spiritually"--